À propos des drachmai argyriou symmachikou - Psoma, Selene Eleni (Tekmeria, 2019)
The aim of this paper is to collect all the evidence on the drachmai argyriou symmachikou in two distinct groups of epigraphic documents: the first includes documents from Miletus and Colophon that date from the last fifteen years of the 4th cent. BC and the second includes documents from Boeotia and Arcadia that date from the 2nd/1st cent. BC. The symmachikai drachmai of therst documents are interpreted in the context of the alliance of Antigonus-the-one-Eyed with a number of cities of Asia Minor after his declaration of the freedom of the Greek cities in Tyros. These symmachikai drachmai were coins of Persian weight that were issued by a number of cities during this period. The drachmai symmachikou of the second group were the Rhodian imitations struck by a number of cities that participated in the wars between Rome, the Antigonids and the Seleucids. The paper discusses and takes into consideration epigraphic documents, hoard and numismatic evidence. It is followed by a discussion on the reference to Corinthian drachms in public documents from Aetolia and Acarnania, Corcyra and Epidamnus and by the suggestion to identify them, not with Corcyrean-weight coinages or coins of Corcyra, but with the Corinthian drachms issued by the city of Corinth during the Hellenistic period and down to 146 BC. The conclusion is based on recently published hoard evidence from Illyria.